Could hatha yoga be a health-related physical activity? - Grabara Małgorzata (Sciendo, 2016)
The objectives of this review paper are (I) the analysis based on previous studies of whether hatha yoga exercises fulfil the recommendation for the level of physical activity recommended by the WHO and ACSM; (II) the recommendation for how to arrange weekly hatha yoga practice, which can be considered a health-related physical activity; and (III) the analysis of the benefits of a regular hatha yoga workout in view of scientific studies, in particular regard to the prevention of diseases of civilization and improvement in health-related physical fitness.